2011
DOI: 10.3390/su3101986
|View full text |Cite
|
Sign up to set email alerts
|

Energy Return on Energy Invested for Tight Gas Wells in the Appalachian Basin, United States of America

Abstract: Abstract:The energy cost of drilling a natural gas well has never been publicly addressed in terms of the actual fuels and energy required to generate the physical materials consumed in construction. Part of the reason for this is that drilling practices are typically regarded as proprietary; hence the required information is difficult to obtain. We propose that conventional tight gas wells that have marginal production characteristics provide a baseline for energy return on energy invested (EROI) analyses. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
1
12
0
2
Order By: Relevance
“…Conversely, the NEER is a more useful measure of the contribution of an energy source to the energy supply of society because it counts only the inputs that must be produced and delivered externally through the existing energy supply system. The NEER form used herein is consistent with a recent study by Sell and colleagues (). These authors provide the relationship, as shown in equation , EROI =(normalPnormals)/(normalS+normalC+normalp+normalD)where P is production, s is shrinkage, and the (S + C + p + D) denominator represents steel, cement, proppant, and diesel fuel, which, they say, represent the chief energy inputs of the extraction effort.…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…Conversely, the NEER is a more useful measure of the contribution of an energy source to the energy supply of society because it counts only the inputs that must be produced and delivered externally through the existing energy supply system. The NEER form used herein is consistent with a recent study by Sell and colleagues (). These authors provide the relationship, as shown in equation , EROI =(normalPnormals)/(normalS+normalC+normalp+normalD)where P is production, s is shrinkage, and the (S + C + p + D) denominator represents steel, cement, proppant, and diesel fuel, which, they say, represent the chief energy inputs of the extraction effort.…”
Section: Methodssupporting
confidence: 81%
“…However, some gas plays have a higher EROI; vertical tight gas wells in the Appalachian basin in Pennsylvania, which are typically hydraulically fractured, have been found to have an EROI in the range of 67:1 to 120:1 (Sell et al ). (A “play” is a known or postulated gas or oil accumulation sharing similar geologic, geographic, and temporal properties.)…”
Section: Introductionmentioning
confidence: 99%
“…It has obviously made a tremendous contribution to China's oil industry and has maintained a long-term stable yield. Compare EROI POU of China's conventional fossil fuels with EROI of unconventional fossil fuels [34][35][36][37][38][39][40][41] from another country, it can be seen that the EROI for China's conventional fossil fuels is lower than the EROI of unconventional fossil fuels based on current literature. Figure 6 also shows the EROI of U.S. shale oil & gas and China's conventional oil & gas.…”
Section: Resultsmentioning
confidence: 99%
“…Almost all these analyses have shown that the EROI for oil and gas is high but is decreasing. Other papers have focused on other energy resources, such as coal (Cleveland et al, 1984;Hu et al, 2013), shale gas (Aucott and Melillo, 2013;Yaritani and Matsushima, 2014), tight gas (Sell et al, 2011), oil shale (Brandt, 2008(Brandt, , 2009Cleveland and O'Connor, 2011), hydropower (Weißbach et al, 2013;Atlason and Unnthorsson, 2014b), wind (Brown and Ulgiati, 2002;Wagner and Pick, 2004), bio-fuels (Atlason and Unnthorsson, 2014b;Weißbach et al, 2013), wind (Brown and Ulgiati, 2002;Wagner and Pick, 2004), bio-fuels (Agostinho and Ortega, 2013;Aitken et al, 2014), and solar (Dale and Benson, 2013;Kubiszewski et al, 2009;Raugei et al, 2012). However, the peer-reviewed literature has paid only minimal attention to the EROIs of SNG (EROI SNG ) and ING (EROI ING ).…”
Section: Literature Reviewmentioning
confidence: 96%